Near-Infrared Responsive Phase-Shifted Nanoparticles for Magnetically Targeted MR/US Imaging and Photothermal Therapy of Cancer - Xu, Yan (Front Bioeng Biotechnol, 2020)
Accurate diagnosis, providing guidance for early treatment, can greatly improve the survival rate of cancer patients. However, there are still some difficulties with the existing diagnostic technology and early treatment methods. Here, near-infrared responsive phase-shifted nanoparticles (NRPNs) have been designed for magnetically targeted MR/US imaging and photothermal therapy of tumors. In this study, we fabricated a multifunctional polymer nanoparticle encapsulating indocyanine green (ICG), magnetic Fe(3)O(4) nanoparticles and perfluoropentane (PFP). Under laser irradiation, the NRPNs, which trigger a phase-shifted expansion effect due to the quick conversion from light to heat by ICG and Fe(3)O(4), can be used for ultrasound (US) imaging. At the same time, such nanoparticles can kill cancer cells via photothermal therapy (PTT). As a kind of negative enhancement agent, magnetic Fe(3)O(4) nanoparticles in NRPNs showed high spatial resolution in MR imaging. Moreover, with the help of the magnetic field, the NRPNs nanoparticles showed high cellular uptake and high tumor accumulation, indicating their magnetic targeting property without biosafety concerns. Therefore, we present a strategy for magnetically targeted MR/US imaging guided photothermal therapy for the accurate diagnosis and efficient treatment of tumors.